Lenalidomide maintenance fails to overcome the unfavourable prognosis of low NK‐cell counts in rituximab–chemotherapy responsive elderly DLBCL patients: A LYSA group study. (6th February 2023) - Beldi‐Ferchiou, Asma; Jais, Jean‐Philippe; Ghesquieres, Hervé; Casasnovas, Rene Olivier; Tilly, Hervé; Fruchart, Christophe; Morschhauser, Franck; Haioun, Corinne; Lazarovici, Julien; Perrot, Aurore; Nicolas‐Virelizier, Emmanuelle; Salles, Gilles; et al.
Summary: Low baseline NK‐cell counts (NKCCs) in patients with diffuse large B‐cell lymphoma (DLBCL) are associated with a poor prognosis. The REMARC phase III trial (NCT01122472) showed that lenalidomide maintenance prolonged PFS in rituximab–chemotherapy responders. We conducted a REMARC ancillary study analysing the impact of lenalidomide maintenance on the prognostic value of low NKCCs. Blood samples from 335 elderly French patients enrolled in the REMARC trial were analysed by flow cytometry to obtain NKCCs at diagnosis ( n = 220), at randomization ( n = 186) and/or six months after randomization ( n = 184). Baseline NKCCs < 100 cells/μl were associated with shorter PFS and OS (HRs = [2.2 (1.4, 3.3), p < 0.001] and [2.8 (1.7, 4.5), p < 0.001], respectively), independently of aaIPI. In a competing risk analysis, low NKCCs at baseline were associated with a higher risk of relapse/progression ( p = 0.0025), but not of death without progression ( p = 0.33). Lenalidomide did not affect the prognosis value of low baseline NKCCs ( p = 0.6349). Similar results were obtained for low NKCCs at randomization. Our results demonstrate that low NKCCs at baseline and post rituximab–chemotherapy are robust prognostic factors in DLBCL and reveal that lenalidomide has no impact on this parameter. Other therapeutic strategies aiming at improving NK‐cell function could improve outcomes in DLBCL.